Kurikulum Tersembunyi Dalam Pembelajaran Pendidikan Agama Islam - Caswita, Caswita (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2019)
AbstractThe purpose of this study was to examine the curriculum application that integrated between the written curriculum and the hidden curriculum at SD Al-Muttaqin Tasikmalaya. This is qualitative research with a study case approach. The data were collected by interviewing, observing, and analyzing documents conducted at al-Muttaqin elementary school in Tasikmalaya. Secondary sources found out from the books, journals, articles and other scientific works. Based on the research findings, the results of this study indicate that were: (1) the school was giving low attention to the hidden curriculum in PAI’s learning whereas the hidden curriculum had a significant effect on the success of PAI’s learning. (2) PAI’s learning which combines between the written curriculum and the hidden curriculum will produce more applicable and contextual learnings. The findings of this study indicate that was SD al Muttaqin as a private Islamic school has implemented the curriculum that combines between the written curriculum and the hidden curriculum has been implemented well, and it is was producing active learning. This is proven from the achievements of the PAI that always being superior to another school in the city of Tasikmalaya.AbstrakArtikel ini bertujuan untuk mengkaji penerapan kurikulumm yang mengintegrasikan antara kurikulum tertulis (written curriculum) dan kurikulum tersembunyi (hidden curriculum) di SD al-Muttaqin Tasikmalaya. Penelitian ini menggunakan pendekatan kualitatif dengan pendekatan studi kasus. Sumber data diperoleh dengan cara wawancara, observasi, dan analisis dokumen yang dilakukan pada sekolah dasar al-Muttaqin di Tasikmalaya. Sumber sekunder berupa buku-buku, jurnal, artikel serta karya ilmiah lainnya. Temuan penelitian ini menunjukkan, pertama sekolah kurang memperhatikan hidden kurikulum dalam pembelajaran PAI padahal hidden kurikulum sangat besar pengaruhnya terhadap keberhasilan pembelajaran PAI. Kedua, pembelajaran PAI yang memadukan antara kurikulum tertulis dan kurikulum tersembunyi akan menghasilkan pembelajaran yang lebih aplikatif dan kontekstual. Temuan penelitian ini menunjukan bahwa SD al Muttaqin sebagai sekolah swasta Islam telah menerapkan kurikulum yang memadukan antara tertulis (written curriculum) dan kurikulum tersembunyi (hidden curriculum) dengan baik, sehingga menghasilkan pembelajaran yang efektif. Hal tersebut terbukti dari prestasi bidang PAI selalau unggul dibanding dengan sekolah lain yang ada di kota Tasikmalaya.